2023
DOI: 10.1186/s12916-023-03011-5
|View full text |Cite
|
Sign up to set email alerts
|

Adverse associations between maternal deoxynivalenol exposure and birth outcomes: a prospective cohort study in China

Tianqi Tan,
Tingting Chen,
Wenwen Zhu
et al.

Abstract: Background Deoxynivalenol (DON), one of the most prevalent mycotoxins, has been found to cause fetal growth retardation in animals. However, limited evidence exists regarding its effects on pregnant women. Methods Maternal urinary concentration of total DON (tDON) and free DON (fDON) in the second trimester was measured using liquid chromatography with tandem mass spectrometry. Provisional daily intake (PDI) of DON was calculated based on tDON conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In a study of the mycotoxin content of amniotic fluid samples (n = 86), DON was found in 27.9% of samples [28]. Maternal DON exposure, in turn, appears to adversely affect fetal development [29]. In a recent prospective cohort study by Tan et al (2023), mothers in the highest tertile of DON intake were more likely to have infants with lower birth weights and decreased birth lengths that were low for the infant's gestational age (all P-trends < 0.05) [29].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of the mycotoxin content of amniotic fluid samples (n = 86), DON was found in 27.9% of samples [28]. Maternal DON exposure, in turn, appears to adversely affect fetal development [29]. In a recent prospective cohort study by Tan et al (2023), mothers in the highest tertile of DON intake were more likely to have infants with lower birth weights and decreased birth lengths that were low for the infant's gestational age (all P-trends < 0.05) [29].…”
Section: Introductionmentioning
confidence: 99%